2007
DOI: 10.1016/j.jacc.2007.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Serum Myeloperoxidase Levels Are Associated With the Future Risk of Coronary Artery Disease in Apparently Healthy Individuals

Abstract: Elevated MPO levels predict future risk of CAD in apparently healthy individuals. This study suggests that inflammatory activation precedes the onset of overt CAD by many years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
244
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 390 publications
(264 citation statements)
references
References 29 publications
11
244
0
9
Order By: Relevance
“…MPO levels have been shown in multiple studies to track with incident risks of CVD events in subjects (53,(55)(56)(57). The present studies may help to explain prior reports of pro-inflammatory HDL in the acute phase setting, as well as during chronic inflammation such as in CVD.…”
Section: Discussionsupporting
confidence: 60%
“…MPO levels have been shown in multiple studies to track with incident risks of CVD events in subjects (53,(55)(56)(57). The present studies may help to explain prior reports of pro-inflammatory HDL in the acute phase setting, as well as during chronic inflammation such as in CVD.…”
Section: Discussionsupporting
confidence: 60%
“…Last, MPO is secreted by activated leukocytes and is thought to mediate oxidative stress and atherogenesis 42. It has been associated with future coronary disease and HF in case‐control studies 43, 44. In our study, MPO predicted incident HF, in addition to all‐cause mortality.…”
Section: Discussionmentioning
confidence: 50%
“…Although there is a suggestion that MPO may be produced by atherosclerotic macrophages, there is also evidence that MPO may be derived from neutrophils in the vascular wall in atherosclerosis [72]. It has been demonstrated that the measurement of MPO levels may be useful in risk stratification of patients with atherosclerosis [78,79]. In addition, MPO polymorphism studies have demonstrated an increased risk for cardiovascular events in patients with chest pain [80].…”
Section: Pathophysiology Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 99%